Skin preparation and its manufacturing method

The external skin agent, composed of specific cellulose fibers, hydroxyethylcellulose, and water-soluble salts, addresses the challenge of maintaining high viscosity and skin feel in the presence of salts, achieving excellent salt resistance and skin compatibility.

JP7650645B2Active Publication Date: 2025-03-25DKS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020189813
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-13
Publication Date
2025-03-25
Estimated Expiration
2040-11-13

AI Technical Summary

Technical Problem

Existing external skin agents, such as cosmetics and pharmaceuticals, face challenges in maintaining high viscosity and excellent feel on the skin when exposed to salts, as they lack sufficient salt resistance.

Method used

The external skin agent comprises cellulose fibers with a number average fiber diameter of 2 to 150 nm, carboxy groups introduced at a ratio of 0.6 to 3.0 mmol/g, hydroxyethylcellulose, water-soluble organic salts or inorganic salts, and water, which together provide excellent salt resistance and skin feel.

Benefits of technology

This formulation achieves excellent salt resistance, maintaining high viscosity and providing an excellent feel on the skin, even when containing salts, thus enhancing its usability in cosmetic and pharmaceutical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650645000001
    Figure 0007650645000001
  • Figure 0007650645000002
    Figure 0007650645000002
  • Figure 0007650645000003
    Figure 0007650645000003
Patent Text Reader

Abstract

To provide external preparations for skin having high halotolerance and a good feeling of use to the skin.SOLUTION: According to one embodiment, external preparations for skin contain the following components (A)-(D): (A) cellulose fibers with a number average fiber diameter of 2-150 nm, the cellulose fibers having a cellulose I crystal structure, with carboxy groups introduced at a rate of 0.6-3.0 mmol / g; (B) hydroxyethyl cellulose of 5-500 mass% relative to the mass of (A); (C) a water-soluble organic salt and / or water-soluble inorganic salt; (D) water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an external skin preparation and a method for producing an external skin preparation. [Background technology]

[0002] It is known that cellulose nanofibers, which are cellulose fibers reduced to nano-size, are used as thickeners in external skin preparations such as cosmetics, pharmaceuticals, and quasi-drugs.

[0003] For example, Patent Document 1 discloses a viscous aqueous composition that is excellent in usability and can achieve high viscosity even when the amount of thickener used is reduced, the viscous aqueous composition containing cellulose fibers having a number average fiber diameter of 2 to 150 nm and carboxyl groups introduced at a ratio of 0.6 to 2.0 mmol / g, a thickening promoter, and water. Patent Document 1 describes nonionic thickening polysaccharides, acrylic polymers, and cellulose derivatives having a weight average molecular weight of 120,000 or more as thickening promoters, and specifically exemplified tamarind gum, glucomannan, guar gum, carboxyvinyl polymer, alkyl (meth)acrylate copolymer, carboxymethylcellulose, methylcellulose, and hydroxyethylcellulose. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-126788 A Summary of the Invention [Problem to be solved by the invention]

[0005] As mentioned above, Patent Document 1 lists various thickening promoters to be combined with cellulose fibers, but does not disclose that the use of hydroxyethyl cellulose improves salt tolerance. In cosmetics, pharmaceuticals, and other skin topical preparations, formulations containing inorganic salts, organic salts, and other salts may be used, and even in such cases, it is desirable to maintain high viscosity such as a cream or gel, i.e., to have excellent salt tolerance.

[0006] An object of the present invention is to provide an external skin preparation that has excellent salt tolerance and excellent feel on the skin when used. [Means for solving the problem]

[0007] The present invention includes the embodiments set forth below. [1] A skin preparation containing the following ingredients (A) to (D): (A) Cellulose fibers having a number average fiber diameter of 2 to 150 nm, the cellulose fibers having a cellulose I type crystal structure, and having carboxyl groups introduced at a ratio of 0.6 to 3.0 mmol / g. (B) 5 to 500% by mass of hydroxyethyl cellulose relative to the mass of component (A). (C) A water-soluble organic salt and / or a water-soluble inorganic salt. (D) Water. [2] The topical skin preparation according to [1], wherein the content of the component (A) is in the range of 0.1 to 2 mass % based on the total amount of the topical skin preparation. [3] The topical skin preparation according to [1] or [2], wherein the viscosity of a 2% by mass aqueous solution of component (B) is 10 to 8,000 mPa s when measured using a Brookfield viscometer at 6 rpm, 25°C, and for 3 minutes. [4] A method for producing an external preparation for skin according to any one of [1] to [3], comprising obtaining a dispersion in which the component (A) is dispersed in the component (D), and adding the component (B) to the dispersion before adding the component (C). Effect of the Invention

[0008] According to an embodiment of the present invention, it is possible to provide an external skin preparation that has excellent salt tolerance and excellent feel on the skin when used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The topical skin preparation of this embodiment contains a specific cellulose fiber as component (A), hydroxyethyl cellulose as component (B), a water-soluble organic salt and / or a water-soluble inorganic salt as component (C), and water as component (D).

[0010] [(A) Cellulose fiber] As the cellulose fibers, cellulose nanofibers (CNF) that satisfy the following (a1) to (a3) ​​are used. (a1) The number average fiber diameter is 2 to 150 nm. (a2) Having a cellulose type I crystal structure. (a3) Carboxy groups are introduced at a ratio of 0.6 to 3.0 mmol / g.

[0011] Regarding (a1) above, since the fiber diameter of the cellulose single nanofiber, which is the basic unit of the cellulose fiber, is about 2 nm, the number average fiber diameter of the cellulose fiber is preferably 2 nm or more. The upper limit of the number average fiber diameter of the cellulose fiber is 150 nm or less, so that the viscosity increase property and transparency can be improved. The number average fiber diameter of the cellulose fiber is preferably 2.5 nm or more, and more preferably 3 nm or more. The number average fiber diameter of the cellulose fiber is preferably 100 nm or less, more preferably 50 nm or less, even more preferably 20 nm or less, and may be 10 nm or less.

[0012] The maximum fiber diameter of the cellulose fibers is not particularly limited, but from the viewpoint of improving the feel on the skin, it is preferably 1000 nm or less.

[0013] The average aspect ratio of the cellulose fibers is not particularly limited, and may be, for example, 30 or more, 50 or more, or 100 or more. The average aspect ratio may also be 700 or less, or 500 or less.

[0014] The number average fiber diameter of cellulose fibers is calculated by arithmetically averaging the fiber diameters of 50 cellulose fibers randomly selected in image observation by atomic force microscope (AFM). The average aspect ratio is calculated by arithmetically averaging the fiber lengths of the 50 cellulose fibers to calculate the number average fiber length, and is calculated as the ratio of the number average fiber length to the number average fiber diameter (number average fiber length / number average fiber diameter). The maximum fiber diameter is the fiber diameter of the cellulose fiber having the largest fiber diameter in the image taken by the atomic force microscope when measuring the number average fiber diameter.

[0015] Regarding the above (a2), the cellulose type I crystal structure refers to the crystalline form of natural cellulose. The cellulose type I crystal structure can be identified by the presence of typical peaks at two positions, around 2θ=14° to 17° and 2θ=22° to 23°, in a diffraction profile obtained by wide-angle X-ray diffraction image measurement.

[0016] Regarding (a3) ​​above, the cellulose fibers according to this embodiment are carboxy-modified cellulose fibers in which cellulose molecules are chemically modified so that glucose units, which are constituent units of the cellulose molecules, have carboxy groups.

[0017] One or more carboxy groups may be bonded to all glucose units constituting the cellulose molecule, or one or more carboxy groups may be bonded to some of the glucose units constituting the cellulose molecule.

[0018] The carboxy group may be directly or indirectly bonded to the glucose unit. When the carboxy group is indirectly bonded, for example, an alkylene group having 1 to 4 carbon atoms may be present between the glucose unit and the carboxy group.

[0019] In this specification, the term "carboxy group" refers not only to the acid type (-COOH) but also to the salt type, i.e., carboxylate group (-COOX, where X is a cation that forms a salt with a carboxylic acid), and the acid type and the salt type may be mixed. The salt is not particularly limited, and examples thereof include alkali metal salts such as sodium salts and potassium salts, alkaline earth metal salts such as magnesium salts and calcium salts, onium salts such as ammonium salts and phosphonium salts, and amine salts such as primary amines, secondary amines, and tertiary amines.

[0020] The content of carboxy groups in the cellulose fibers (carboxy group amount) is 0.6 to 3.0 mmol / g per dry mass of the cellulose fibers. When the carboxy group amount is 0.6 mmol / g or more, the cellulose fibers can be dispersed to single nanofiber units, and cellulose fibers having an average fiber diameter of 2 to 150 nm can be obtained. When the carboxy group amount is 3.0 mmol / g or less, the cellulose fibers are not water-soluble and can maintain the crystal structure of cellulose type I. The carboxy group amount is preferably 1.0 mmol / g or more, and preferably 2.5 mmol / g or less. In this specification, the "dry mass" refers to the mass after drying at 140°C until the mass change rate per minute becomes 0.05% or less.

[0021] Examples of cellulose fibers having carboxy groups include oxidized cellulose fibers obtained by oxidizing the hydroxyl groups of the glucose units in the cellulose molecules, and carboxymethylated cellulose fibers obtained by carboxymethylating the hydroxyl groups of the glucose units in the cellulose molecules.

[0022] Oxidized cellulose fibers include those in which the hydroxyl group at the C6 position of the glucose unit in the cellulose molecule is selectively oxidized to a carboxyl group. Oxidized cellulose fibers are obtained by oxidizing natural cellulose such as wood pulp using a co-oxidant in the presence of an N-oxyl compound and then subjecting the cellulose to a fine refinement treatment. As the N-oxyl compound, a compound having a nitroxy radical, which is generally used as an oxidation catalyst, is used, for example, a piperidine nitroxyoxy radical, and in particular, 2,2,6,6-tetramethylpiperidinooxy radical (TEMPO) or 4-acetamide-TEMPO is preferred. The oxidized cellulose fibers may have an aldehyde group or a ketone group in addition to the carboxyl group.

[0023] The micronization treatment to obtain the number average fiber diameter of (a1) above can be carried out by treating an aqueous dispersion of cellulose fibers using, for example, a homomixer, a high-pressure homogenizer, an ultrasonic dispersion processor, a beater, a disk refiner, a conical refiner, a double disk refiner, a grinder, or the like at high speed rotation, to obtain an aqueous dispersion of fine fibrous cellulose fibers.

[0024] In the skin topical preparation according to the present embodiment, the content of the cellulose fiber of the component (A) is not particularly limited, and may be, for example, 0.01 to 10% by mass, or 0.05 to 5% by mass, based on the total amount of the skin topical preparation, and is preferably 0.1 to 2% by mass. By making the cellulose fiber content 0.1% by mass or more, the effect of improving salt tolerance can be enhanced. By making the cellulose fiber content 2% by mass or less, the feeling on the skin during use can be further improved.

[0025] [(B) Hydroxyethyl cellulose] Hydroxyethyl cellulose (HEC) is a water-soluble polymer obtained by adding ethylene oxide to cellulose. By using hydroxyethyl cellulose together with the cellulose fiber of component (A), it is possible to improve the salt tolerance of the skin topical preparation and improve the feel of the skin when used.

[0026] The content of hydroxyethyl cellulose is preferably 5 to 500% by mass relative to the mass of the cellulose fiber, which is the component (A). By making the content relative to the mass of the component (A) 5% by mass or more, salt resistance can be improved, and by making the content relative to the mass of the component (A) 500% by mass or less, the feeling on the skin during use can be improved. The content of hydroxyethyl cellulose relative to the mass of the component (A) is preferably 10% by mass or more, more preferably 50% by mass or more, and is preferably 300% by mass or less, more preferably 200% by mass or less.

[0027] Hydroxyethyl cellulose is preferably one having a viscosity of 10 to 8000 mPa·s in a 2% by mass aqueous solution when measured using a B-type viscometer at 6 rpm, 25°C, and 3 minutes. When the viscosity is 10 mPa·s or more, the effects of salt resistance and high viscosity can be enhanced. When the viscosity is 8000 mPa·s or less, the effects of feeling on the skin and salt resistance can be enhanced. The viscosity is preferably 20 mPa·s or more, and more preferably 6000 mPa·s or less. The viscosity can be adjusted by the degree of polymerization (i.e., average molecular weight) of hydroxyethyl cellulose, the average number of moles of ethylene oxide added, and the like. Various hydroxyethyl celluloses having different viscosities are commercially available, and one may be selected from them for use, or may be prepared based on a known method.

[0028] [(C) Water-soluble organic salt and / or water-soluble inorganic salt] The skin external preparation according to this embodiment contains either one or both of a water-soluble organic salt and a water-soluble inorganic salt.Though it contains a water-soluble organic salt and / or a water-soluble inorganic salt, it has excellent salt resistance due to the combination of the (A) component and the (B) component, and can maintain the thickening effect of these salts.The solubility of these water-soluble organic salts and water-soluble inorganic salts in water is sufficient as long as they can be dissolved in water at the concentration at which they are incorporated in the skin external preparation.

[0029] The water-soluble organic salt is not particularly limited, and various water-soluble organic salts that are incorporated into skin external preparations can be used, such as alkali metal salts (sodium salts, potassium salts, etc.), alkaline earth metal salts (magnesium salts, calcium salts, etc.), and ammonium salts of organic acids (preferably organic acids having 10 or less carbon atoms). In one embodiment, specific examples of the water-soluble organic salt include citrates such as sodium citrate, L-ascorbyl phosphate salts such as sodium L-ascorbyl phosphate salts, ascorbyl salts such as calcium ascorbate salts, ethylenediaminetetraacetates such as disodium ethylenediaminetetraacetate salts, and dehydroacetates such as sodium dehydroacetate salts. Any one of these may be used, or two or more may be used in combination.

[0030] The water-soluble inorganic salt is not particularly limited, and includes various water-soluble inorganic salts that are incorporated into external skin preparations, such as chlorides such as NaCl, KCl, CaCl2, and MgCl2, sulfates such as (NH4)2SO4, carbonates such as Na2CO3 and K2CO3, and nitrates such as KNO3. Any of these may be used alone or in combination of two or more.

[0031] The content of the water-soluble organic salt and / or water-soluble inorganic salt is not particularly limited, and may be, for example, 0.01% by mass or more, 1.0% by mass or more, and 10.0% by mass or less, or 5.0% by mass or less, based on the total amount of the topical skin preparation.

[0032] [(D)Water] In the topical skin preparation of this embodiment, the water content is not particularly limited and may be, for example, 30% by mass or more, 50% by mass or more, 80% by mass or more, 90% by mass or more, or 99% by mass or less, or 98% by mass or less, relative to the total amount of the topical skin preparation.

[0033] [External skin preparations] The skin topical agent according to this embodiment is an aqueous composition, in which the cellulose fiber of component (A) is dispersed in the water of component (D). The water-soluble organic salt and / or water-soluble inorganic salt of component (C) are dissolved in the water of component (D), and therefore the dispersion medium in which the dispersoid of component (A) is dispersed is an aqueous solution of the water-soluble organic salt and / or water-soluble inorganic salt. Hydroxyethyl cellulose of component (B) is water-soluble, and therefore is dissolved in the water of component (D). Preferably, component (B) is adsorbed to the surface of cellulose fiber, which is component (A). This is believed to prevent aggregation of component (A) by component (C), and enhance the effect of improving salt tolerance.

[0034] The skin topical preparation according to the present embodiment may contain other ingredients in addition to the above-mentioned (A) to (D) ingredients. The other ingredients are not particularly limited, and may include, for example, additives such as active ingredients, oily raw materials, surfactants, moisturizing agents, organic fine particles, inorganic fine particles, antioxidants, preservatives, UV absorbers, pigments, dyes, deodorants, fragrances, and organic solvents, depending on the intended use of the skin topical preparation. These may be used alone or in combination of two or more kinds.

[0035] When an oily raw material is included, the skin topical agent may be an oil-in-water type (O / W type) emulsion composition in which the oily raw material is emulsified in water. Examples of the oily raw material include various liquids that separate from water, such as silicone oils such as methylpolysiloxane and cyclopentasiloxane; vegetable oils such as avocado oil and olive oil; animal oils such as fish oil and beef tallow; waxes such as carnauba wax and lanolin; hydrocarbons such as squalane and mineral oil; higher fatty acids such as oleic acid and linoleic acid; higher alcohols such as isostearyl alcohol and oleyl alcohol; ester oils such as fatty acid esters and triglycerides; aromatic alcohols such as benzyl alcohol and phenethyl alcohol. These may be used alone or in combination of two or more.

[0036] The viscosity of the topical skin preparation is not particularly limited since it varies depending on the concentration, application, etc., but the viscosity at a liquid temperature of 25°C is preferably 2 mPa·s or more, more preferably 500 mPa·s or more, even more preferably 1000 mPa·s or more, and may be 3000 mPa·s or more. The upper limit of the viscosity of the topical skin preparation is not particularly limited, but may be, for example, 300,000 mPa·s or less, or 100,000 mPa·s or less. Here, the viscosity is a value measured using a Brookfield viscometer under conditions of 6 rpm, 25°C, and 3 minutes.

[0037] The topical skin preparation according to this embodiment is preferably prepared by dispersing component (A) in component (D) and then adding component (B) before adding component (C).

[0038] That is, in one embodiment of the manufacturing method, first, an aqueous dispersion of cellulose fibers is prepared by dispersing cellulose fibers (A) in water (D). Next, hydroxyethyl cellulose (B) is added to the obtained aqueous dispersion and dissolved. After that, a water-soluble organic salt and / or a water-soluble inorganic salt (C) is added to the aqueous dispersion in which the component (B) is dissolved and dissolved. By adding the component (B) before adding the component (C) in this way, the component (B) is easily adsorbed to the surface of the cellulose fibers (A), and the effect of improving salt resistance can be enhanced. The timing of addition of the other components is not particularly limited, and for example, they may be added together with the component (C) or after the addition of the component (C).

[0039] The use of the skin external preparation according to this embodiment is not particularly limited, and examples thereof include cosmetics, external medicines, quasi-drugs, etc., having a formulation such as cream or gel. Specifically, the skin external preparation can be used for cold cream, vanishing cream, massage cream, emollient cream, cleansing cream, pack, foundation, sunscreen cosmetic, suntan cosmetic, moisture cream, hand cream, etc., skin cosmetics, shampoo, rinse, hair conditioner, rinse-in shampoo, hair styling agent (hair foam, gel-type hair styling agent, etc.), hair treatment agent (hair cream, treatment lotion, etc.), hair cosmetics such as hair dye, hair growth agent, hair care agent, and cleaning agent such as hand cleaner, ointment, patch, etc. EXAMPLES

[0040] Examples will be described in detail below together with comparative examples. However, the present invention is not limited to these examples. In the examples, "%" means by mass unless otherwise specified.

[0041] [Preparation of cellulose fiber A1] 150 mL of water, 0.25 g of sodium bromide, and 0.025 g of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) were added to 2.0 g of softwood kraft pulp, and the mixture was thoroughly stirred. Then, a 13% aqueous solution of sodium hypochlorite was added so that the amount of sodium hypochlorite was 12 mmol / g per 1.0 g of the pulp, and the reaction was started. The reaction was continued for 120 minutes while a 0.5 N aqueous solution of sodium hydroxide was added dropwise to maintain the pH at 10 to 11 during the reaction. After the reaction, 0.1 N hydrochloric acid was added to adjust the pH to 2.0, and the solid-liquid separation was performed by suction filtration. Pure water was added to the solid content to prepare a slurry with a solid content concentration of 2.0%. The pH was then adjusted to 10 with a 10% aqueous solution of sodium hydroxide, and 0.2 mmol / g of sodium borohydride was added to the cellulose fiber, and the mixture was reacted for 2 hours for reduction treatment. After the reaction, the mixture was neutralized by adding 0.1N hydrochloric acid, and purified by repeatedly filtering and washing with water. Pure water was added to the obtained purified product to prepare a slurry with a solid content of 2.0%, and the pH was adjusted to 7 with a 10% aqueous sodium hydroxide solution. Then, a micro-fine processing step was performed using a microfluidizer (150 MPa, 1 pass) to obtain an aqueous dispersion of cellulose fiber A1.

[0042] [Preparation of cellulose fiber A2] An aqueous dispersion of cellulose fibers A2 was obtained in the same manner as in the preparation of cellulose fibers A1, except that the amount of the aqueous sodium hypochlorite solution added was 6 mmol / g per 1.0 g of the pulp.

[0043] [Preparation of cellulose fiber A3] An aqueous dispersion of cellulose fibers A3 was obtained in the same manner as in the preparation of cellulose fibers A1, except that the number of passes through the microfluidizer in the micronization treatment step was 10.

[0044] [Preparation of Cellulose Fiber B1 (Comparative Example)] An aqueous dispersion of cellulose fiber B1 was obtained in the same manner as for preparing cellulose fiber A1, except that the raw material was changed from softwood kraft pulp to regenerated cellulose and the amount of sodium hypochlorite solution added was changed to 27.0 mmol / g per 1.0 g of regenerated cellulose.

[0045] [Evaluation of cellulose fibers] The cellulose fibers A1 to A3 and B1 were used to measure the number average fiber diameter, the amount of carboxyl groups and the crystal structure according to the following evaluation methods. The measurement methods are as follows. The results are shown in Table 1 below.

[0046] (1) Number average fiber diameter In image observation using an atomic force microscope (AFM), a dozen cellulose fibers were randomly selected from an image of 1 μm square, and the fiber diameter was measured. The number-average fiber diameter (nm) was calculated by averaging the fiber diameters of a total of 50 cellulose fibers from multiple images taken at different positions.

[0047] (2) Crystal structure A diffraction profile was obtained by wide-angle X-ray diffraction image measurement, and the structure with peaks at two positions, near 2θ=14°-17° and near 2θ=22°-23°, was identified as type I crystal structure, and the structure with peaks at near 2θ=10-14° and near 2θ=20-22° was identified as type II crystal structure.

[0048] (3) Carboxy group content 0.25 g of cellulose fiber was dispersed in water to prepare 60 mL of cellulose aqueous dispersion, and the pH was adjusted to approximately 2.5 with 0.1 N hydrochloric acid, after which 0.05 N aqueous sodium hydroxide solution was added dropwise and electrical conductivity was measured. Measurements were continued until the pH reached 11. In the stage of neutralization of the weak acid, where the change in electrical conductivity is gradual, the amount of carboxyl groups was calculated from the amount of sodium hydroxide (V) consumed according to the following formula. Amount of carboxyl group (mmol / g) = V (mL) × [0.05 / mass of cellulose fiber (g)]

[0049] [Table 1]

[0050] For the cellulose fibers A1 to A3, it was confirmed that the largest fiber diameter (that is, the maximum fiber diameter) in the image taken with an atomic force microscope when measuring the number average fiber diameter was 1000 nm or less.

[0051] [Preparation of topical skin preparation] Using the aqueous dispersions of cellulose fibers A1 to A3 and B1 obtained by the above-mentioned preparation method, a mixed solution for use as an external skin preparation was prepared.

[0052] [Example 1] 25 g of the aqueous dispersion of cellulose fiber A1 was weighed out, 75 g of pure water was added, and the mixture was stirred at 8000 rpm for 10 minutes using a homomixer MARKII 2.5 type (manufactured by PRIMIX Co., Ltd.) to prepare a diluted solution with a cellulose fiber concentration of 0.5%. 0.05 g of hydroxyethyl cellulose H1 powder was added to the diluted solution, and the mixture was stirred at 8000 rpm for 5 minutes using a homomixer MARKII 2.5 type (manufactured by PRIMIX Co., Ltd.). Furthermore, 2 g of sodium chloride powder was added, and the mixture was stirred at 3000 rpm for 5 minutes using a homodisper 2.5 type (manufactured by PRIMIX Co., Ltd.) to obtain a mixed solution. Hydroxyethyl cellulose H1 had a viscosity of 5200 mPa·s when a 2% aqueous solution was measured using a B-type viscometer at 6 rpm, 25°C, and 3 minutes, and "AW-15F" manufactured by Sumitomo Seika Chemicals Co., Ltd. was used.

[0053] [Comparative Example 1] 25 g of the aqueous dispersion of cellulose fiber A1 was weighed out, 75 g of pure water was added, and the mixture was stirred at 8,000 rpm for 10 minutes using a Homomixer MARKII 2.5 type (manufactured by PRIMIX) to obtain a diluted solution with a cellulose fiber concentration of 0.5%. 2 g of sodium chloride powder was then added to the diluted solution, and the mixture was stirred at 3,000 rpm for 5 minutes using a Homodisper 2.5 type (manufactured by PRIMIX) to obtain a mixed solution.

[0054] [Examples 2 and 3 and Comparative Example 2] A mixed solution was obtained in the same manner as in Example 1, except that the amount of hydroxyethyl cellulose H1 powder added (mass% relative to cellulose fiber (represented as "mass% relative to CNF" in Table 2)) was adjusted as shown in Tables 2 and 4 below.

[0055] [Examples 4 and 5] A mixed solution was obtained in the same manner as in Example 1, except that hydroxyethyl cellulose H2 was used instead of hydroxyethyl cellulose H1 in the amounts shown in Table 2. Hydroxyethyl cellulose H2 was "AL-15F" manufactured by Sumitomo Seika Chemicals Co., Ltd., and had a viscosity of 30 mPa s when a 2% aqueous solution was measured using a Brookfield viscometer at 6 rpm, 25°C, and for 3 minutes.

[0056] [Examples 6 and 7] A mixed solution was obtained in the same manner as in Example 1, except that the cellulose fiber concentration and the amount of hydroxyethyl cellulose H1 added were adjusted as shown in Table 2.

[0057] [Examples 8 and 9] A mixed solution was obtained in the same manner as in Example 1, except that the type of cellulose fiber and the amount of hydroxyethyl cellulose H1 added were changed as shown in Table 3.

[0058] [Example 10] A mixed solution was obtained in the same manner as in Example 1, except that the salt added was changed from sodium chloride to sodium L-ascorbate phosphate and the amount of hydroxyethyl cellulose H1 added was changed as shown in Table 3.

[0059] [Example 11] A mixed solution was obtained in the same manner as in Example 1, except that the salt added was changed from sodium chloride to sodium citrate, and the amount of hydroxyethyl cellulose H1 added was changed as shown in Table 3.

[0060] [Comparative Example 3] A mixed solution was obtained in the same manner as in Example 1, except that hydroxypropyl cellulose H3 was used instead of hydroxyethyl cellulose H1 in the amounts shown in Table 4. Hydroxypropyl cellulose H3 was "hydroxypropyl cellulose" manufactured by Tokyo Chemical Industry Co., Ltd., and had a viscosity of 4500 mPa s when a 2% aqueous solution was measured using a Brookfield viscometer at 6 rpm, 25°C, and for 3 minutes.

[0061] [Comparative Example 4] A mixed solution was obtained in the same manner as in Example 1, except that hydroxypropyl methylcellulose H4 was used instead of hydroxyethyl cellulose H1 in the amounts shown in Table 4. Hydroxypropyl methylcellulose H4 had a viscosity of 4200 mPa s when a 2% aqueous solution was measured using a Brookfield viscometer at 6 rpm, 25°C, and for 3 minutes, and "Metolose" manufactured by Shin-Etsu Chemical Co., Ltd. was used.

[0062] [Comparative Example 5] A mixed solution was obtained in the same manner as in Example 1, except that carboxymethyl cellulose C1 ("Cellogen" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was used in place of hydroxyethyl cellulose H1 and was blended in the amounts shown in Table 4.

[0063] [Comparative Example 6] A mixed solution was obtained in the same manner as in Example 1, except that methylcellulose C2 (Metolose, manufactured by Shin-Etsu Chemical Co., Ltd.) was used in place of hydroxyethylcellulose H1 and was blended in the amounts shown in Table 4.

[0064] [Comparative Example 7] A mixed solution was obtained in the same manner as in Example 1, except that xanthan gum C3 ("KELTROL" manufactured by CP Kelco) was used in place of hydroxyethyl cellulose H1 and was blended in the amounts shown in Table 5.

[0065] [Comparative Example 8] A mixed solution was obtained in the same manner as in Example 1, except that pectin C4 ("PHRESH" manufactured by CP Kelco) was used in place of hydroxyethyl cellulose H1 and was blended in the amounts shown in Table 5.

[0066] [Comparative Example 9] A mixed solution was obtained in the same manner as in Example 1, except that carboxyvinyl polymer P1 ("Carbopol" manufactured by Lubrizol) was used in place of hydroxyethyl cellulose H1 and was blended in the amounts shown in Table 5.

[0067] [Comparative Example 10] A mixed solution was obtained in the same manner as in Example 1, except that polyvinyl alcohol P2 (Poval, manufactured by Kuraray Co., Ltd.) was used in place of hydroxyethyl cellulose H1 and was blended in the amounts shown in Table 5.

[0068] [Comparative Example 11] A mixed solution was obtained in the same manner as in Example 1, except that the type of cellulose fiber was changed to cellulose fiber B1 and the amount of hydroxyethyl cellulose H1 added was changed as shown in Table 5.

[0069] [Evaluation of topical skin preparations] The viscosity, salt resistance, TI value, and feel were evaluated for Examples 1 to 11 and Comparative Examples 1 to 11. The evaluation methods were as follows.

[0070] (1) Viscosity The mixed liquids obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were transferred to 100 mL sample bottles and allowed to stand overnight at room temperature, after which the viscosity was measured using a B-type viscometer (6 rpm, 25° C., 3 minutes).

[0071] (2) Salt tolerance The mixed solutions obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were subjected to the same procedure except that no salt was added to prepare mixed solutions not containing salt. After each mixed solution was left to stand for one day after preparation, the viscosity was measured using a twin drive rheometer MCR302 (manufactured by Anton Paar). The shear rate was 100 sec -1The viscosity at this time was taken as the measured value, and the viscosity retention rate before and after the addition of salt was calculated using the following formula. The higher the viscosity retention rate, the better the salt resistance. Viscosity retention rate [%] = (viscosity of mixture containing salt) / (viscosity of mixture without salt) x 100

[0072] (3) TI value The viscosity of the mixed liquids obtained in Examples 1 to 11 and Comparative Examples 1 to 11 was measured using a twin drive rheometer MCR302 (manufactured by Anton Paar) with the shear rate as a variable. From the measurement results obtained, the thixotropic index (TI value) was calculated using the following formula. TI value = (0.01sec -1 Viscosity at 0.1 sec -1 Viscosity at

[0073] (4) Feel (feeling of use) The mixed liquids obtained in Examples 1 to 11 and Comparative Examples 1 to 11 were applied to the upper arm and dried, and the feel was evaluated according to the following criteria. The results of the feel were calculated by adding up the scores of five in-house monitors, and the total score was judged according to the following criteria. 4 points: Not sticky 2 points: A little sticky 0 points: Very sticky Total score: 0-4 points: ×, 5-9 points: △, 10-14 points: ○, 15-20 points: ◎

[0074] [Table 2]

[0075] [Table 3]

[0076] [Table 4]

[0077] [Table 5]

[0078] The results are shown in Tables 2 to 5. Comparing Examples 1 to 3 with Comparative Example 1, it was found that the addition of hydroxyethyl cellulose H1 improved salt resistance, and the greater the amount of hydroxyethyl cellulose added, the better the salt resistance. This is believed to be because hydroxyethyl cellulose is adsorbed onto the surface of the cellulose nanofibers, preventing aggregation due to inorganic salts. In this regard, when the mixed solutions of Examples 1 to 3 were dried and the fiber diameter of the cellulose fibers was observed using an atomic force microscope (AFM), it was confirmed that the fiber diameter was several nm thicker than the original cellulose fiber A1, and it is believed that hydroxyethyl cellulose is adsorbed onto the surface of the cellulose fibers.

[0079] In addition, a comparison between Examples 1 to 3 and Comparative Example 1 revealed that the addition of hydroxyethyl cellulose did not have a significant effect on the TI value of the mixed solution. In other words, it is believed that the viscosity characteristics of the mixed solution are dominated by the cellulose nanofibers, regardless of the presence or absence of the addition of hydroxyethyl cellulose. Furthermore, a similar tendency was observed in all of Examples 4 and 5, which had different types of hydroxyethyl cellulose, Examples 6 and 7, which had different cellulose fiber concentrations, Examples 8 and 9, which had different types of cellulose fiber, and Examples 10 and 11, which contained an organic salt.

[0080] On the other hand, referring to Comparative Example 2, it can be seen that when a large amount of hydroxyethyl cellulose H1 was added, the salt tolerance was excellent, but the stickiness characteristic of thickening polysaccharides became strong and the feel was impaired.

[0081] In addition, referring to Example 2 and Comparative Examples 3 to 10, it is suggested that when hydroxyethyl cellulose is used among various water-soluble polymers, both the salt resistance and the feel of the mixed solution are excellent. In Comparative Examples 3 to 8, when other water-soluble celluloses or thickening polysaccharides are used, some of them have the effect of improving the salt resistance of the mixed solution, but they are very sticky and have a poor feel when applied to the skin. Hydroxyethyl cellulose with a certain viscosity or less is less thickening than these other water-soluble celluloses and thickening polysaccharides, and is less sticky, so it is considered to have an excellent feel. In Comparative Example 9, carboxyvinyl polymer (carbomer) improves the viscosity of the mixed solution and provides a good feel, but the salt resistance is greatly reduced. This is thought to be due to the fact that carbomer has an anionic functional group, and when the salt concentration increases, the molecular chain shrinks, causing both the cellulose nanofibers and the carbomer to aggregate. In Comparative Example 10, polyvinyl alcohol cannot significantly improve the salt resistance, and the feel is somewhat sticky.

[0082] In Comparative Example 11, it was not possible to prepare a viscous mixed liquid using regenerated cellulose, and it was therefore impossible to evaluate salt tolerance.

[0083] As described above, the skin topical preparation according to the embodiment has excellent salt resistance, and therefore, although it contains salts such as organic salts and inorganic salts, it can suppress viscosity reduction and maintain high viscosity such as creamy or gel-like, and has excellent usability when applied to the skin.In addition, since it is also excellent in safety, it can be suitably used in the fields of cosmetics, medicines, quasi-drugs, etc., where these properties are required.

[0084] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included in the scope and gist of the invention as well as the invention and its equivalents described in the claims.

Claims

1. A skin topical preparation containing the following components (A) to (D), in which the content of component (C) is 0.01 to 10.0% by mass based on the total amount of the skin topical preparation: (A) Cellulose fibers having a number average fiber diameter of 2 to 150 nm, the cellulose fibers having a cellulose I type crystal structure, and having carboxy groups introduced at a ratio of 0.6 to 3.0 mmol / g. (B) 50 to 500% by mass of hydroxyethyl cellulose, based on the mass of component (A). (C) A water-soluble inorganic salt, or a water-soluble organic acid salt and a water-soluble inorganic salt. (D) Water.

2. The topical skin preparation according to claim 1, wherein the content of the component (A) is in the range of 0.1 to 2% by mass based on the total amount of the topical skin preparation.

3. The skin topical preparation according to claim 1 or 2, wherein the viscosity of a 2% by weight aqueous solution of the component (B) is 10 to 8000 mPa·s when measured using a Brookfield viscometer at 6 rpm, 25°C, and for 3 minutes.

4. A method for producing an external skin preparation according to any one of claims 1 to 3, comprising obtaining a dispersion in which the component (A) is dispersed in the component (D), and adding the component (B) to the dispersion before adding the component (C).

Citation Information

Patent Citations

  • Liquid nourishing composition

    JP1997157179A

  • Thickening composition and external preparation for skin comprising the same

    JP2007246667A

  • Viscous aqueous composition

    JP2012126788A

  • Skin cosmetic

    JP2016064996A

  • Cosmetic

    JP2017048142A